(untitled) (Journal of Informatics Education and Research, 2025)
Networking offered a unique value in building a strong professional network for business success. It leverages access to the resources to explore effective networking strategies. It strengthens the funding programs to build trust among stakeholders and women entrepreneurs. The researcher found that women entrepreneurs face a lack of access to digital platforms and ineffective networking. The descriptive and exploratory design was used to analyze the patterns and relationships of women entrepreneurs. The purposive sampling method was used to collect data from 102 respondents through a structured questionnaire. The findings suggest that the women entrepreneurs must develop value chain linkages and collaboration from stakeholders through an inclusive environment.